Chronic cryptosporidiosis in patients with AIDS: stable remission and possible eradication after long-term, low dose azithromycin. Issue 2 (February 1998) - Dionisio, D; Orsi, A; Sterrantino, G; Meli, M; Di Lollo, S; Ibba Manneschi, L; Trotta, M; Pozzi, M; Sani, L; Leoncini, F
Abstract : AIMS: To investigate the effectiveness of long term, low dose azithromycin treatment for chronic cryptosporidiosis in patients with AIDS. METHODS: Azithromycin was administered as initial daily treatment to 13 patients with AIDS: 6 patients received 500 mg for 30 to 40 days (mean 35); 3 patients received 1000 mg for 21 to 50 days (mean 37); and 4 patients received 1500 mg for 20 days. Nine of the 13 patients were also given low dose maintenance treatment with different schedules of azithromycin for 30 to 360 days (mean 129). Patients were monitored, during and after treatment, for parasite shedding in stool and for daily stool frequency and body weight. All but one patient had severe immunodeficiency. RESULTS: Long term, low dose maintenance treatment was associated with major clinical and parasitological benefits: there was probable eradication of infection in 2 patients, and 7 patients showed a complete response with persistent high decrease (5 patients) or clearance (2 patients) of parasite in stool. The drug was well tolerated, and there was no relapse either during treatment or during follow up (up to 21 months). These results were more impressive than those observed after the short term initial course of azithromycin, which was unable at any tested dose to achieve parasite clearance in stool (except in the patient with less advanced immunodeficiency) or to prevent relapse in 3 patients who discontinued treatment. Reversible side effects occurred with the 1500 mg daily dose. CONCLUSIONS: Long term, low dose azithromycin is well tolerated and may induce stable remission of chronic cryptosporidiosis in patients with AIDS. It may lead to probable eradication of the infection in some patients, even those with severe immunodeficiency.